Characterization of mixing in T-jets mixers - Krupa, Kateryna (2019)
The product distribution of a fast chemical reaction system was used for the characterization of micromixing in T-jets mixers; several geometries were assessed under different operational conditions (Reynolds number and jets flow rate ratio). The micromixing test system was the reaction between 1-naphthol and diazotized sulfanilic acid in an aqueous medium. The results obtained show that for all geometries mixing is enhanced with Reynolds number and with the operation at flow rate ratios close to unity. The geometrical parameters of T-jets mixers have a critical influence on the product distribution of the test reaction; particularly the ratio between the mixing chamber width and the inlet jet width, and also the mixing chamber depth. Micromixing is shown to be mainly related to the flow field regime observed at each geometry and operational conditions, which were previously set using Planar Laser Induced Fluorescence.